ETNOVETERINER PERAWATAN DAN PENGOBATAN PENYAKIT HEWAN TERNAK SAPI OLEH MASYARAKAT DESA ANDONGREJO DAN PEMANFAATANNYA SEBAGAI E-BOOKLET INTERAKTIF PADA MATERI KEANEKARAGAMAN HAYATI KELAS X TINGKAT SMA/MA SEDERAJAT - Jesi Kartika Putri; Abdillah Fatkhul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Ethnoveterinary is a traditional livestock treatment practice that represents local wisdom and needs to be documented to preserve indigenous knowledge sustainability. This study aimed to identify medicinal plants used in ethnoveterinary practices, describe cattle treatment techniques, analyze the Use Value (UV) and Informant Consensus Factor (ICF), and validate an interactive e-booklet as a learning medium for Biodiversity materials in Grade X Senior High School. This research employed a qualitative approach with an ethnographic method through interviews, observations, and documentation. The results identified 24 species of medicinal plants used by the community of Andongrejo Village, with the Zingiberaceae family and rhizomes being the most dominant. Six processing methods were found, with polyherbal formulations becoming a distinctive local treatment practice. UV analysis showed that 11 species had the highest value (UV=1), while diarrhea had the highest ICF value (0.93). The interactive e-booklet achieved a very valid category from media experts (93.00%) and material experts (88.6%), indicating its feasibility as a local wisdom-based learning medium.